Light and temperature as developmental signals in woodland strawberry and red raspberry - Rantanen, Marja (University of Helsinki, 2017)
Plants adjust their development by responding to temperature, photoperiod and light quality as indicators of season and the prevailing environment. Seasonal flowering strawberries (Fragaria sp.) and red raspberry (Rubus idaeus) are temperate species that are typically induced to flower under the short days (SD) that occur in the autumn. Temperature strongly influences the SD effects. Contrary to the seasonal flowering genotypes of these species, long photoperiods advance flowering in ever-bearing genotypes. Woodland strawberry (Fragaria vesca) is a model plant for the garden strawberry (F.× ananassa) and woody Rosaceae plants. The floral repressor FvTERMINAL FLOWER1 (FvTFL1) in the woodland strawberry causes seasonal flowering. Under non-inductive long day (LD) activation of FvFLOWERING LOCUS T1 (FvFT1) >FvSUPPRESSOR OF OVEREXPRESSION OF CONSTANS1 (FvSOC1) > FvTFL1-pathway suppresses flowering. The objective of the research summarised in this thesis was to study how temperature regulates flowering in the woodland strawberry. In addition, the effects of light quality in the woodland strawberry and the tunnel-grown red raspberry were studied at the molecular and physiological levels. Expression studies and transgenic plant approaches showed that FvTFL1 protein integrates the photoperiod and temperature signals in the woodland strawberry. At non-inductive high temperature FvTFL1 is highly activated to suppress flowering. Other regulators than FvSOC1 are involved in the upregulation of the FvTFL1 gene: especially under SD conditions. The FvSOC1 dependent photoperiodic regulation of FvTFL1 has a major role but only at intermediate temperatures. The down-regulation of the FvTFL1 gene allows for flower induction at cool temperatures. The photoperiod response at intermediate temperatures was found to depend on light quality. Long days (LD) and day-length extension with far-red wavelength (FR) light substantially activated the expression of FvFT1, which correlated negatively with flowering in the seasonal flowering woodland strawberry. Under conditions of red wavelength (R) light and SD no FvFT1 mRNA was detected though the plants were induced to flower. In the perpetual flowering accession, the effect of light quality on FvFT1 expression was similar, but the flowering response was opposite. In the absence of functional FvTFL1 protein, the FvFT1 was found to mediate light quality signals and function as an LD dependent floral activator. Light quality also affected flowering in the raspberry in a cultivar dependent manner. The use of an FR absorbing photoselective film led to increased number of flowers in primocane fruiting cultivars (LD plants) and decreased number of flowers in floricane fruiting cultivars (SD plants). This study provides evidence that FvTFL1 has a central role in the integration of temperature and photoperiod signals in regulating flowering in the woodland strawberry. The light quality signal is mediated by FvFT1, but the floral responses of the SD and LD flowering genotypes are opposite and thus, depend on the presence of FvTFL1. The results suggest that the modification of a combination of temperature, photoperiod and light quality is a potential approach to use in controlling vegetative and generative growth in strawberry and raspberry.
Keywords: lämpötila; valon laatu; ambient temperature; light quality; mansikat; valo; lämpö; kukinta; strawberries; flowering